Tensions and support in the academic training process for Social Work students at a public university in south-western Colombia - Burbano Cerón, Mary Hellen; Manco Lozano, Bianca Alejandra; Bastidas Rivera, Stefany (Cuadernos de Trabajo Social, 2021)
This article presents the findings of a qualitative study carried out in order to understand the times in the academic training process that caused most tension among the students in an academic social work programme at a public university in the city of Cali, located in south-western Colombia. The main forms of support used by students to remain in the academic programme are also identified. As a result, it is reported that the most tense moments during the academic training process – interpreted as structural testing (Martuccelli, 2006) – were joining and adjusting to university, the study of certain subjects and academic practice. When faced with these tensions, university students resorted to the use of internal or individual support and also external sources, mainly institutional, such as peer support (from other students) and relationships with teachers at their institution. The study findings suggest the importance of including strategies to reinforce links among peers and teachers in university retention programmes.
Keywords: university student retention; academic training; social work; tensions and support